2003
DOI: 10.1128/mcb.23.17.6000-6012.2003
|View full text |Cite
|
Sign up to set email alerts
|

Expression ofMISin the Testis Is Downregulated by Tumor Necrosis Factor Alpha through the Negative Regulation of SF-1 Transactivation by NF-κB

Abstract: The expression of Mullerian inhibiting substance (MIS),Mullerian inhibiting substance (MIS), also known as antiMullerian hormone (AMH), is essential in normal sex differentiation and reproductive function (for a review, see reference 48). Its expression is tightly regulated in tissue-specific and development-specific manners. MIS expression in the testis is restricted to Sertoli cells and is high in fetal-to-prepubertal mice, but it becomes low in pubertal-to-adult mice. Previous studies have suggested that MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
2
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 62 publications
(57 reference statements)
3
45
2
1
Order By: Relevance
“…7A). On the other hand, the SF-1 activity repressed by p65 was recovered by TSA treatment, as previously reported (22). We confirmed the TSA insensitivity of the NF-B repression of Nur77 transactivation with a native steroidogenic-enzyme P450c17 gene promoter.…”
Section: Downloaded Fromsupporting
confidence: 76%
See 3 more Smart Citations
“…7A). On the other hand, the SF-1 activity repressed by p65 was recovered by TSA treatment, as previously reported (22). We confirmed the TSA insensitivity of the NF-B repression of Nur77 transactivation with a native steroidogenic-enzyme P450c17 gene promoter.…”
Section: Downloaded Fromsupporting
confidence: 76%
“…Whole-cell extracts were prepared after a 6-h treatment with TNF-␣, and immunoprecipitations were carried out using anti-Nur77 and anti-SF-1 antibodies. Western blot analysis of the immunoprecipitated material revealed that, in response to TNF-␣, the Nur77-p65 complex did not recruit HDACs, whereas the SF-1-p65 complex recruited HDAC4 but not HDAC1, as previously reported (22).…”
Section: Downloaded Fromsupporting
confidence: 49%
See 2 more Smart Citations
“…Hsp86 immunohistochemisty showed that the number of male germ cells were significantly decreased in the TSA treated gonadal explants. Testicular germ cells affect MIS expression in Sertoli cells by TNF-α [25]. However, in this study, MIS and SF-1 expressions revealed no change.…”
Section: Discussioncontrasting
confidence: 49%